Magnetic properties of ilmenite used for oxygen carrier aided combustion. (15th May 2023) - Faust, Robin; Lamarca, Ignacio; Schaefer, Andreas; Lind, Fredrik; Knutsson, Pavleta
Highlights: Ilmenite increases in magnetic susceptibility throughout its utilization as bed material. Ilmenite forms magnetite (Fe3 O4 ) which influences the effectiveness of magnetic separation. Attachments of magnetite onto contaminating particles renders them magnetic. Fresh ilmenite can have insufficient magnetic susceptibility for magnetic separation. Abstract: Oxygen carrier aided combustion is a combustion process that utilizes oxygen carrying particles in a fluidized bed to transport oxygen from oxygen-rich to oxygen-poor regions in the reactor. A commonly used oxygen-carrying material is ilmenite (FeTiO3 ) which is a naturally occurring mineral. At higher oxygen partial pressures ilmenite can react to pseudobrookite (Fe2 TiO5 ) and thereby take up oxygen. Upon reduction of pseudobrookite in oxygen-lean locations the oxygen is released, which enhances the distribution of oxygen through the reactor. Ilmenite was used as bed material in an industrial 115 MWth circulating fluidized bed (CFB) boiler where recycled waste wood and wood chips were utilized as fuel. Bottom ash samples were extracted after one and two weeks and the samples were separated into two fractions by a magnetic separator. The magnetic fraction was expected to be enriched in iron-containing oxides and was therefore aimed to be recirculated into the boiler. The SEM-EDS analysis revealed that the non-magnetic fraction consists to the largest extent of feldspar (KAlSi3 O8 ) particles. A significant amount of freshly introduced ilmenite particles was also classified as non-magnetic by the magnetic separator. Characteristic for these particles was a lack of ash layer, suggesting they had only recently been added to the system. In the magnetic fraction, several feldspar particles were found which were covered by a layer rich in Ca, Fe, Ti, and Si. Comparing the XRD analysis of the ash prior to magnetic separation with its magnetic fraction revealed a decrease of the peaks corresponding to feldspar. The removal of feldspar particles by magnetic separation was further corroborated by XRF analysis, where the concentration of K, Al and Si was significantly higher in the non-magnetic fraction, however, no changes were observed in the concentration of Fe. The present analyses shows that prolonged exposure time of ilmenite increases its magnetic susceptibility. Non-magnetic feldspar was shown to acquire significant magnetic susceptibility by formation of a surface layer containing Fe-rich attrition products from ilmenite.